Some Remarks on p^'-Lindelöf Bitopological Spaces - Hanan Almurtadhay; Fatma Alderaz (African Journal of Advanced Pure and Applied Sciences, 2025)
This paper is a presentation to generalize the notion of Lindelöfness in pairwise topological space, we first obtain a new concept of pairwise Lindelöf bitopological space according to -open sets in [7], called -Lindelöf (BTS), under this approach many results could be obtained by examining the relationships between separation axioms, lindelöfness and compactness on pairwise topological spaces.